Research on the Path of Artisan Spirit to Party Ideological Education in Colleges and Universities Based on Image Processing Technology - Bo Wang; Yu Li; Muhammad Talha (Journal of Advanced Transportation)
This research study aims to measure the study analysis on the path of artisan spirit related to party education related to the ideological in colleges and universities. The image processing technology research study describes that primary data related to the artisan spirit performance were gathered using different questions related to the image processing technology. The party ideological education is the dependent variable, and image processing technology includes segmentation quality factors and performance related to the image processing technology. These are considered independent variables. For measuring, the data used AMOS software and run different results related to the party ideological education in college and universities. The character design major has more significant commercial benefits and chances for growth. The investigation and analysis can confirm that the main is appropriately orientated. It maintains continual communication with companies, scheduling, increasing students’ practical competence, and also offers students internship opportunities. The overall results found that the artisan path to party ideological education significantly relates to college and universities based on the image processing technology.